USM ORGANISES WORKSHOP ON MANAGING HEADACHES AND STROKE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, February 2016 – Universiti Sains Malaysia (USM) through its Balance and Stroke Rehabilitation Unit, Audiology Programme, School of Health Sciences (PPSK), has organised a Workshop on Managing Headaches and Strokes by applying ‘solat’ (prayers) therapy.